Agroecology-based analysis of meteorological and agricultural drought using time series remote sensing data in the upper Gelana watershed, Ethiopia - Sileshi Tadesse; Asnake Mekuriaw (Geocarto International)
Drought, a recurrent environmental hazard, poses significant challenges to Ethiopia’s predominantly rainfed, agriculture-based economy, affecting millions of people. This study investigates the characteristics and interrelationships between meteorological and agricultural droughts across lower weina dega (LWD), upper weina dega (UWD), and dega agroecological zones (AEZs) within the upper Gelana watershed, Ethiopia. The results reveal distinct seasonality in meteorological droughts, with the kiremt season exhibiting higher frequency compared to the belg season across all AEZs from 1991 to 2021. The belg-season agricultural droughts were more frequent in LWD, followed by UWD AEZ. Agricultural droughts were also observed in all AEZs during the kiremt seasons in 2002, 2008 and 2009. A statistically significant positive relationship between meteorological and agricultural drought indices was found in both seasons, indicating the potential transmission of meteorological drought into agricultural drought. The findings highlight the need for tailored adaptation strategies suited to the specific conditions of each AEZ.